Returns on EU Funding for Human Capital Development in Rural Areas - Laura Elena MARINAS (Revista de Management Comparat International)
The paper aims to explore at which extent the investments in human capital in rural areas could contribute to rural development and competitiveness. European Union is investing substantial resources for faster growth and competitiveness, addressing the faster development needs of the regions lagging development under cohesion policy. The EU cohesion policy emphasizes the role of the urban areas to reduce disparities in economic development, employment and opportunities between the most advanced and the most disadvantaged areas of the Union, while the rural development pillar under Common Agricultural Policy (CAP) focuses on promoting competitiveness and development of rural areas. Since the economic/social patterns and indicators of the rural areas deviate very much from the average EU values, the goal of reducing the regional development disparities cannot be achieved unless urban and rural development needs are considered together with the cohesion policy. The paper is based on the assumptions that: (a) investments in human capital are recognized as key drivers for competitiveness and development in both urban and rural areas and (b) under scarcity of available resources, the EU funds under cohesion and rural development policies could significantly contribute to human capital development in rural areas. The paper also aims to assess at which extent the EU funds have contributed to human capital development in rural areas and how these investments have benefited to rural development.